2017
DOI: 10.1186/s13256-017-1243-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular findings in a Moroccan family with Jervell and Lange-Nielsen syndrome: a case report

Abstract: BackgroundJervell and Lange-Nielsen syndrome (Online Mendelian Inheritance in Man 220400) is a rare autosomal recessive cardioauditory ion channel disorder that affects 1/200,000 to 1/1,000,000 children. It is characterized by congenital profound bilateral sensorineural hearing loss, a long QT interval, ventricular tachyarrhythmias, and episodes of torsade de pointes on an electrocardiogram. Cardiac symptoms arise mostly in early childhood and consist of syncopal episodes during periods of stress, exercise, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…So far, 21 different homozygous or compound heterozygous mutations in KCNQ1 gene and 3 homozygous or compound heterozygous mutations in KCNE1 gene in JLNS patients have been characterized according to the Human Genome Database (HGMD), http://www.hgmd.cf.ac.uk/ac/index.php) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, 21 different homozygous or compound heterozygous mutations in KCNQ1 gene and 3 homozygous or compound heterozygous mutations in KCNE1 gene in JLNS patients have been characterized according to the Human Genome Database (HGMD), http://www.hgmd.cf.ac.uk/ac/index.php) …”
Section: Discussionmentioning
confidence: 99%
“…16 So far, 21 different homozygous or compound heterozygous mutations in KCNQ1 gene and 3 homozygous or compound heterozygous mutations in KCNE1 gene in JLNS patients have been characterized according to the Human Genome Database (HGMD), http://www.hgmd.cf.ac.uk/ac/index.php). 17 In this study, we have identified a homozygous frameshift mutation in exon 5 (c.733-734delGG) of the KCNQ1 gene in 2 nonconsanguineous families with JLNS among an Iranian cohort of LQTS patients. The mutation has not been reported previously in HGMD and 1000 genomes databases.…”
Section: Ge Netic Studymentioning
confidence: 99%
“…Jervell and Lange-Nielsen syndrome was found in a Moroccan family that presented with congenital severe bilateral sensorineural HI. The affected patient had several episodes of syncope and was diagnosed with an associated KCNQ1 (c.1343dupC, p.Glu449Argfs*14) variant (Adadi et al 2017).…”
Section: Jervell and Lange-nielsen Syndromementioning
confidence: 99%